The Effect of 360° Performance Appraisal on Employees Intention to Stay with Career Development as a Mediating Variable: Evidence from a Teaching Hospital in Depok City: JEL Classification: M12, M54, J63, J24, I11 - Latyfa Cania Armys; Hendrik Heri Sandi (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
Human resources are a crucial element in ensuring the sustainability and quality of healthcare services. In hospitals, maintaining Employee Intention to Stay is important to support service continuity and organizational stability. However, high work pressure and limited career development opportunities may reduce employees’ intention to remain in the organization. This study aims to examine the effect of 360° performance appraisal on Employee Intention to Stay with career development as a mediating variable at a teaching hospital in Depok City. This study employed a quantitative causal research design. Data were collected through questionnaires distributed to 180 employees. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3.2.9. The results indicate that 360° performance appraisal does not have a significant direct effect on Employee Intention to Stay. However, 360° performance appraisal has a significant positive effect on career development, and career development significantly influences Employee Intention to Stay. Furthermore, career development mediates the relationship between 360° performance appraisal and Employee Intention to Stay. These findings suggest that the effectiveness of performance appraisal influences Employee Intention to Stay indirectly through career development within the organization.